Understanding the determinants of self-service technology (SST) adoption in fast-food chain setting - Gu, Weiwei (2017)
In today’s business environment, the way that people interact with service providers has been witnessed a dramatic change. Service encounter has been gradually substituted by technology-based self service. Self checkout system, as one of the most important type of SST, has been widely adopted in different industries, such as hotel, supermarket, oil pump station, etc. However, limited success has been witnessed in a fast-food restaurant setting. In particular, the success of SST adoption from a customer perspective is unclear. Thus, the main purpose of this study is to examine a customer evaluation model including attitude, satisfaction and re-use intention of SST by identifying key antecedents. Besides, this study further delivered managerial implications to practitioners who run fast-food business aiming to address the practical issues. A quantitative method was used to investigate these issues by generating solid and insightful findings though SPSS analysis. The findings suggest that various antecedents offer different levels of explanatory power toward consequences (attitude, satisfaction and intention). The explanatory power also varies from different demographic factors (e.g. age group, education level). From this perspective, this study offered directions that marketing practitioners should focus on and put effort in, and helped them to understand the evaluation process of SST from a customer perspective. Finally, the limitation of this research was also discussed in the end of study.